Intraoperative local flap transforming (iLoFT) method; from hachet to reading-man flap. (June 2017) - Kato, Motoi; Kimura, Shinnosuke; Okochi, Masayuki; Ueda, Kazuki; Watanabe, Shoji; Watanabe, Azusa; Kono, Tatsuki
Abstract: Local flaps are widely used in soft tissue reconstruction because they result in good colour and texture match. They can be quickly placed without donor site morbidity. However, it is not always easy to preoperatively design a feasible procedure, predict the final scar line or image the tension that may occur on and around the flap, especially for inexperienced surgeons. Because the elasticity of the skin varies with anatomical location and among individuals, unpredictable intraoperative design changes are sometimes required. Therefore, a preoperative back-up plan would be helpful. We evaluated the possibilities and advantages of an intraoperative switch from a hatchet flap (HF) to a reading man flap (RMF) procedure. Using a previously reported computer simulation with the finite element method (FEM) analysis, we developed an intraoperative local flap transformation (iLoFT) model.